Love On The Different Spectrum: A Phenomenological Study On A Young Adult - Reyes, Honey Gem V.; Mirador, Ma. Kaila Theresa R.; Tamondong, Wilhem B.; Ramirez, Alexis Graza; Dela Cruz, Hanna May Custodio; Mangalus, Andrea Reyes (Academic Journal of Psychology and Counseling, 2025)
People with Autism Spectrum Disorder (ASD) have often been wrongly viewed as asexual. However, research suggests that their romantic and sexual experiences are more nuanced and deserving of further exploration. The study aimed to foster a more supportive and understanding environment for individuals with ASD as they navigate the complexities of relationships. This study delved into the romantic and sexual lives of a young man with ASD aged 22 years old to understand how his condition influenced his partner preferences and relationships with friends, classmates, and family. Through a semi-structured interview and interpretative phenomenological analysis (IPA), the study uncovered three key themes: (a) navigating social interactions and boundaries; (b) understanding love and relationships; and (c) desires and expectations in relationships. These insights highlighted the need for tailored sex education, family support, and positive media portrayals. According to the study, a young man with ASD has difficulty interacting socially, particularly when it comes to recognizing cues and establishing limits with others. His romantic aspirations may be impacted by his inability to comprehend emotions and societal prejudices. The results show that to normalize his experiences and promote healthy relationships, family support, specialized sex education, and favorable media portrayals are essential.